Напрями співпраці України та Європейського Союзу щодо міграційних питань - Лаба, О.; Laba, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено етапи формування спільної міграційної політики України та Європейського Союзу, розкрито зміст основних політичних документів, що визначають напрями та інструменти політики ЄС та України у сфері міграції, викладено норми законодавства, прийнятого на їх виконання. Проаналізовано співпрацю України з Європейським Союзом у галузі регулювання міграційних процесів та запропоновано окремі рекомендації, реалізація яких сприяла б удосконаленню міграційної політики України у відповідності до європейських стандартів.The article considers the stages of setting up a joint migration policy of Ukraine and the European Union, the content of the main political documents, which define the directions and policy instruments of the EU and Ukraine in the field of migration, describes the norms of legislation adopted to promote and facilitate their implementation. In the focus of attention is cooperation between Ukraine and the European Union in the management of migration processes and certain recommendations, implementation of which would help to improve Ukraine's migration policy in compliance with European standards. The recommendations are worked out in terms of the perspective of abolition of the visa regime for Ukrainians, deepening the relations with various countries of the EU as a result of the association, which will inevitably intensify cross-border mobility in the western direction. The article places importance on the need for implementation of the acquis communautaire in the subsequent integration of Ukraine with the EU. Thus the study of the developments and the use of EU migration policy seem to be extremely important.
Areas and Trends of Cooperation between Ukraine and the European Union on Migration Issues.
Keywords: міграційна політика; європейські стандарти; біженці; міграційний простір; Шенгенська зона; мігранти; співпраця; візовий режим; нелегальна міграція; migration policy; European standards; refugees; migration space; Schengen area; migrants; cooperation; visa regime; illegal migration